Analisis dan Penerapan Enterprise Resource Planning (ERP) Odoo 10 guna membuat Laporan Keuangan pada Yayasan Darul Jannah - Rosy Annisa Firlana; Suhendi Suhendi (Jurnal Informatika Terpadu, 2020)
The rapid development of technology has made many foundations adopt the latest information technology to help run their business. This writing discusses the application of Odoo application to input payment transactions for students to create financial reports. This application is implemented to facilitate student payment transactions and make it easier to make financial reports. This application uses the Odoo application version 10 and uses the Accounting and Finance module. The research method used is the method of field studies using collecting data from interviews by the principal of TPA Darul Jannah. Testing of this system was carried out using Microsoft Edge. A survey by filling out a questionnaire was conducted to determine user satisfaction with the Odoo system. So it can be concluded that the Odoo system is quite helpful in inputting payment transactions for santri to print financial reports.